Framework for estimating active brain sources using MUSIC and Root MUSIC - Jatoi, M.A. (Institute of Electrical and Electronics Engineers Inc., 2017)
Subspace techniques are widely used for direction of arrival (DOA) problems in telecommunications and position location applications for estimating the location of sources from where the signal is originated. This source estimation problem is analogues to the source estimation problem in EEG signal processing commonly termed as EEG inverse problem. The EEG inverse problem goes for estimation of active source inside the brain which is responsible for overall electromagnetic activity. This estimation provides useful basis to understand the physiological, neural and cognitive behavior of human brain which ultimately can be used for cure of many CNS related disease such as epilepsy and tumour etc. This research discuss most commonly used subspace techniques such as Multiple Signal classifier (MUSIC) and Root MUSIC for general DOA problem and produces some results by using MATLAB for arbitrary number of sources and varied number of element. Thus, the same methodology can be adopted for localization of active brain sources with few exceptions such as forward head modeling and sensor positions. © 2017 IEEE.